MARKCLOUD - Software for data confidentiality and security in cloud computing environments - Olanrewaju, Rashidah Funke; Hakak, Saqib Iqbal; Khalifa, Othman Omran (2014)
Cloud computing is one of the most recently emerged technology which offers resource on demand facility. Cloud computing is an information technology deployment model that involves entrusting data to information systems managed by external parties on remote servers or 1Cin the cloud. 1D In cloud, resources, in terms of infrastructure, applications and data are deployed via the internet as a distributed service by service provider, which make use of applications without installations. This technology allows much more efficient computation by centralizing storage, memory, and processing as well as band width. However, despite the surge in activity and interest, there are significant, persistent concerns about confidentiality and security of data in cloud computing that prevented business organizations from fully accepting cloud platforms. In this paper, cloud computing security issues have been addressed. In addition, and equally importantly, an algorithm has been proposed that can be used between service providers and data owners to safeguard multi-way authentications and tighten access control for sensitive data in both public and private cloud.